Disclosure of genetics research results after the death of the patient participant: a qualitative study of the impact on relatives. - Ormondroyd, E; Moynihan, C; Watson, M; Foster, C; Davolls, S; Ardern-Jones, A; Eeles, R (2007)
When a gene mutation is identified in a research study following the death of the study participant, it is not clear whether such information should be made available to relatives. We report here an evaluation of the impact on relatives of being informed of study results that detected pathogenic BRCA2 mutations in a male relative, now deceased, who had early onset (under the age of 55) prostate cancer. The breast and ovarian cancer risk was unknown to the living relatives. Qualitative analysis of interviews with thirteen relatives indicated that those who had a higher risk perception, resulting from an awareness of cancer family history or experiential knowledge of cancer in their family, tended to adjust more easily to the results. All participants believed that genetics research results of clinical significance should be fed back to relatives. Those who were fully aware of the BRCA2 results and implications for themselves felt they had benefited from the information, irrespective of whether or not they had elected for genetic testing, because of the consequent availability of surveillance programs. Initial anxiety upon learning about the BRCA2 result was alleviated by genetic counselling. Factors influencing those who have not engaged with the information included scepticism related to the relative who attempted to inform them, young age and fear of cancer. Those who had not sought genetic counselling did not attempt further dissemination, and some were not undergoing regular screening. Implications for informed consent in genetics research programs, and the requirement for genetic counselling when research results are disclosed, are discussed.